Prevention of cigarette smoking in adolescents - Abdollahi, Abbas; Abu Talib, Mansor (Lambert Academic Publishing, 2014)
Smoking is the biggest threat to public health, and it remains a serious cause of death in the world. It even causes acute and chronic diseases in passive smokers. Remarkably, the age of the onset of cigarette smoking is decreasing. Therefore, it is essential to increase our knowledge concerning the attitudes among adolescents toward cigarette smoking. The book seeks to examine the role of hardiness and emotional intelligence with attitude towards cigarette smoking in adolescents. The findings showed that hardiness and emotional intelligence were protective factors against smoking in adolescents. Therefore, these findings reinforce the importance of hardiness training and emotional intelligence training in preventing cigarette smoking in adolescents.